Association of variants in APOL1, MYH9 and HMOX1 WITH micro-Albuminuria among Sickle Cell disease patients from Cameroon - Geard, Amy (Division of Human Genetics, 2017)
Introduction: Sickle Cell Disease (SCD) is a monogenic, multi-organ hemoglobinopathy disorder that is highly prevalent in Africa, with nearly 300 000 newborn cases per year. The underlying pathophysiological mechanism of the disease involves alteration of the normal soft and biconcave disc shape of erythrocytes, to that of a rigid crescent. These abnormal red blood cells cause vaso-occlusion and intravascular hemolysis, resulting in a variety of clinical manifestations, including acute pain crises, anemia, and damage to various organs. Kidney disease is a clinical proxy of severity, developing only in a subset of patients, and is subject to modification by genetic variations. Indeed, reports have shown significant association between proteinuria and specific genetic variants in MYH9 and APOL1, and between estimated Glomerular Filtration Rate (eGFR) and End Stage Kidney Disease (ESKD) with HMOX1 variants among adult African Americans affected by SCD. However, the association between these variants and micro-albuminuria, a primary indicator of renal dysfunction, has not been investigated, nor has any study of these variants been performed among SCD patients in Africa. Aim: The aim of this study was to investigate the association of targeted single nucleotide polymorphisms (SNPs) in APOL1, MYH9 and HMOX1, as well as a 5' promoter dinucleotide repeat in HMOX1, with micro-albuminuria among SCD patients from Cameroon; and to compare the results to that from a cohort of non-SCD Cameroonian individuals affected by ESKD.